Non-Polynomial Spline Method For A Singularly Perturbed Convection-Dominated Diffusion Equation - Çağlar, Hikmet; Uçar, Mehmet Fatih; Yıldırım, Mesut (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
In this study, a singularly perturbed convection-dominated diffusion equation is solved by using a non-polynomial spline method. An example is solved to assess the accuracy of the method. The numerical results are obtained for different perturbed values (epsilon) of equation. The results indicate that non-polynomial spline method is effectively implemented. It is seen that results are compatible with exact solutions and consistent with other existing numerical methods.
Keywords: Perturbed convection-dominated diffusion equation; non-polynomial spline; Tedirgin konveksiyon hakim difüzyon denklemi; olmayan polinom spline